1993
DOI: 10.1093/jnci/85.20.1685
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cremophor EL Following Taxol: Plasma Levels Sufficient to Reverse Drug Exclusion Mediated by the Multidrug-Resistant Phenotype

Abstract: The efficacy of paclitaxel against some tumors may be aided by its administration in a vehicle solution containing Cremophor in quantities that reach concentrations in the plasma sufficient to reverse multidrug resistance of neoplastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…It has been proposed to induce a cell cycle block distinct from that seen with paclitaxel (9) or to reverse the multidrug resistance phenotype (10,11). However, it is uncertain whether the plasma concentration of CrEL attainable during Taxol infusion is relevant in solid tumors (4,12,13). Collectively, the addition of CrEL is closely related with toxicity, inconvenience, less effective biodistribution, and special devices for the administration of paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed to induce a cell cycle block distinct from that seen with paclitaxel (9) or to reverse the multidrug resistance phenotype (10,11). However, it is uncertain whether the plasma concentration of CrEL attainable during Taxol infusion is relevant in solid tumors (4,12,13). Collectively, the addition of CrEL is closely related with toxicity, inconvenience, less effective biodistribution, and special devices for the administration of paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the pharmacokinetics of Cremophor EL in patients is limited. A previous paper using a bio-assay reported Cremophor EL levels up to 0.2% (Webster et al, 1993;Rischin et al, 1996). However, our preliminary information using the HPLC assay has revealed that the Cremophor EL levels are much higher (Sparreboom et al, 1996b;Van Tellingen et al, 1996).…”
mentioning
confidence: 71%
“…Blank plasma was spiked with 1.0 ml ml À1 cremophor EL and run as an inter-assay control. This concentration of cremophor EL caused approximately 50% inhibition of maximum daunorubicin accumulation (Webster et al, 1993). The accuracy of the control was always 475%.…”
Section: Assays For Biologic Activitymentioning
confidence: 82%